Persepsi Konsumen Terhadap Peraturan Gubernur Bali No.97 Tahun 2018 Tentang Pembatasan Timbulan Sampah Plastik Sekali Pakai di Kecamatan Mendoyo, Jembrana, Bali - Triyasmita, Ni Komang Mei; Indrayani, Luh (Jurnal Pendidikan Ekonomi Undiksha, 2021)
The purpose of this study is to identify consumer perception towards Bali Governor Regulation Number 97 of 2018 on restrictions of disposable plastic waste. This research used a descriptive type research to analyze consumer perception towards Bali Governor Regulation Number 97 of 2018 on restrictions of disposable plastic waste. The population in this study include all consumers in Mendoyo Subdistrict, Jembrana Regency, Bali. This research used incidental sampling techniques which and obtained samples as many as 330 people. The results of this study were categorized in several dimensions namely dimension of need which obtained a score of 4,144 in the score range of 3,366 - 4,158 thus it is categorized as highly favorable, dimension of expectation obtained a score of 16,603 in the score range of 14,586 - 18,018 thus it is categorized as highly favorable, and dimension of experience obtained a score of 6,625 in the score range of 5,147 - 6,731 thus it is categorized as favorable.